Analysis of Regency and City Regional Development in Central Sulawesi Province, 2016-2020 - Ika Rafika; Rita Suirlan; Muhtar Tallesang; Nurnaningsih Nurnaningsih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine analysis of Regency and City Regional Development in Central Sulawesi Province from 2016 to 2020. The research location is determined in Central Sulawesi Province which includes 12 Regencies and 1 City, considering that the Regional Development in Central Sulawesi Province as seen from the economic performance indicators shows relatively high economic growth but is not followed by a reduction in the number of poor people and the number of unemployed as well as an increase in the human development index because this area will be a pillar in the transfer of the national capital. The data used in the study used panel data. Data analysis in this study used descriptive analysis. The results showed that the economic growth of Central Sulawesi Province in 2016 to 2020 showed a declining percentage with the highest growth occurring in 2018 of 20.20 percent and economic growth in 2020 of 4.86 percent. The expected length of schooling and the average length of schooling in Central Sulawesi Province increase every year. The trend of life expectancy from 2016 to 2020 in Central Sulawesi Province shows a positive development every year but is below the national life expectancy. In 2020, the per capita expenditure of the population in Central Sulawesi Province is around 9.335 thousand rupiah per year. This per capita expenditure figure did increase from 2016 to 2019. However, compared to 2020, this per capita expenditure experienced a significant decline.